Explanations for weight loss after ileojejunal bypass in gross obesity. Issue 6024 (19th June 1976) - Pilkington, T R; Gazet, J C; Ang, L; Kalucy, R S; Crisp, A H; Day, S
Abstract : Twenty grossly obese patients underwent ileojejunal bypass operations. Measurements of calories lost in faeces showed that the malabsorption could not account for the weight loss. Furthermore, the malabsorption was not decreased two years after bypass, when weight was no longer being lost. Dietary restriction is therefore largely responsible for the weight loss and increased food intake for weight maintenance.